USING AUTHENTIC MATERIALS IN ESP CLASSROOMS - Nilufar Soliyevna Nosirova; Dusiyorov Temurbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article deals with the authentic materials in the ESP classroom. Authentic materials are especially important for ESP trainees, since they reproduce an immersion environment and provide a realistic context for tasks that relate to learner’s needs. Authentic materials increase learners’ motivation but are difficult to adapt to the learners’ level of language, especially at the beginning level. It is also important to note that preparing such materials can be very time-consuming.